STRENGTH ANALYSIS OF COMPENSATOR REINFORCED BY WIRE CLOTH UNDER STATIC-RANDOM VIBRATION COMBINED CONDITIONS - YANG Yan; HE QiLin; SI HuiLiu; ZHU HaiYang; WANG Qi; REN MingFa (Jixie qiangdu)
Aiming at the complicated microstructure of the wire cloth in the compensator reinforced by wire cloth and the complicated interaction between the wire cloth and the bellow during service, the strength analysis of the compensator reinforced by wire cloth under the static-random vibration compound condition is established. The equivalent beam model is used to establish the finite element analysis model of the wire cloth. According to the working environment and mechanical performance characteristics of the compensator reinforced by wire cloth, a contact-coupling hybrid analysis method is established. The contact relationship between the bellow and the wire cloth is used in static conditions to simulate the non-linear interaction with the bellow. In the random vibration conditions, the interaction between the wire cloth and the bellow is established by coupling the radial degree of freedom of the wave peak of the bellow and the wire cloth in setting the coupling equation. The error between the static and dynamic analysis results of the model and the static and dynamic test results of the compensator with wire cloth is about 10%. The strength performance analysis of the compensator with wire cloth under the combined condition of static and random vibration analysis is carried out, and the influence of random vibration excitation in different directions on the compensator with wire cloth is discussed. The results show that the X-direction excitation has the greatest impact on the structure; the stress at the first wave peak of the bellow is the largest, which is a weak link in the structure.